Pengaruh PerlakuanUap Etanolterhadap Mutu dan Masa Simpan Buah Manggis (Garcinia Mangostana L.) - I Gusti Ayu Prapti Pundari; I Made Supartha Utama; Ni Luh Yulianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
The aim of this research was to determine the effect of etanol vapor on the quality and the shelf life of mangosteen at the room temperature. Three different volumes of ethanol, namely 0 ml, 2 ml and 4 ml, were trapped in the 5gram carrageenan placed in the tea sachets. The sachet was then put on the basal of styrofoam tray on which 5 fruits were placed and then wraped by streching film LDPE. Control fruits or un-treated fruits were also provided as comparison. The result showed that the ethanol vapor treatments, in general, significantly reduced the intensity of damage, weidght loss, slowing the change rate of texture, color of fruit surface and aril, total soluble solid and vitamin C of the aril, compared to the control fruits. The ethanol vapor was also able to give better preferences of panelists on the color and flavor of the aril, as well as the overall performances of the fruits compared to the controls. The 4 mL ethanol per package created ethanol vapor of which the best vapor to reduce the rate of damage and the change of quality and increase the panelists preferences.